A new semi-implantable middle ear implant for sensorineural hearing loss: three-years follow-up in a pilot patient's group. (2nd January 2018) - Barbara, Maurizio; Volpini, Luigi; Filippi, Chiara; Atturo, Francesca; Monini, Simonetta
Abstract: Objective: The aim of this article is to report on the long-term follow-up of a new semi-implantable middle ear device utilized for restoration of moderate-to-severe sensorineural hearing loss in a first series of subjects. Methods: Three subjects, affected by sensorineural hearing loss, have undergone implantation of Maxum ® middle ear implant, via a transcanal approach. They all underwent an auditory assessment, paying particular attention on the pre- versus post-operative hearing levels under the unaided, best-fitted hearing aided and implant-aided conditions. The audiometric evaluation has been repeated 3 years after implantation and implemented by questionnaires aiming at the evaluation of the quality of life. Results: The post-operative hearing threshold and discrimination in quiet appear to be similar or better than those provided by conventional hearing aids, with a concomitant improvement of the subjects' quality of life. The application of the present device showed to be easy and reproducible, with no severe adverse effects recorded at the 3-years follow-up. Mild issues due to the external component were also observed, such as difficulty of keeping it continuously in place due to excess canal sweating in one subject, and a temporary loss of stability due to occurring irregularities of the external coating in another subject. Conclusions: Long-term, preliminary data reveal that the Maxum ® device may provide equal or better functional gain and word recognition scores in quiet in patients with moderate-to-severe sensorineural hearing loss, in comparison to optimally fitted hearing aids, with a satisfactory improvement of their quality of life.